Roy & Me: This Is Not a Memoir - Maurice Yacowar (Mingling Voices, 2010)
Maurice Yacowar challenges genre and form in Roy & Me, a cross between memoir and fiction, truth and distortion. It is the exploration of Yacowar's relationship with Roy Farran-soldier, politician, author, mentor-and his conflict with Farran's anti-Semitic past. Best known for his service with the British Special Air Service during World War II, Roy Farran served as a politician in the Legislative Assembly of Alberta for Premier Peter Lougheed. During his time in Israel as a soldier, Farran allegedly kidnapped and murdered a sixteen-year-old member of the Lehi group, also known as the Stern Gang. Roy & Me is a memoir that edges toward fiction by venturing into Roy Farran's thoughts, drawing simultaneously on his writings and Yacowar's own imagination.